Vietnam : a case of military obsolescence in developing countries - Wu, Shang-su (2019)
Military obsolescence affects the capability of all militaries as it relates to serviceability and performance when countering potential opponents, and more specifically in the case of developing countries lacking strong indigenous defence industries. The gradual nature of this military concern has not been studied systematically, in contrast to military modernisation. This paper presents a synthetic framework composed of several indicators to examine military obsolescence. Vietnam has been selected for the application of the framework for its large number of Cold War legacies and the strategic pressure from China. Hanoi's ageing assets would undermine its position vis-à-vis Beijing, and its defence investment policies face the dilemma of choosing to spend more on naval and aerial power, or ameliorating its army which is technologically lacking compared to its Chinese counterpart.